Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\left(x+3\right)\left(x-3\right)+x\left(3-x\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x-3\right)-x\left(x-3\right)=0\)
\(\Rightarrow\left(x-3\right)\left(x+3-x\right)=0\)
\(\Rightarrow3\left(x-3\right)=0\)
\(\Rightarrow x-3=0\)
\(\Rightarrow x=3\)
\(b,x\left(x-3\right)+x-3=0\)
\(\Rightarrow\left(x-3\right)\left(x+1\right)=0\)
\(\Rightarrow\hept{\begin{cases}x-3=0\\x+1=0\end{cases}\Rightarrow\hept{\begin{cases}x=3\\x=-1\end{cases}}}\)
Bài giải
\(\left(x-3\right)2-\left(x-3\right)\left(x+3\right)=0\)
\(\left(x-3\right)\left(x+3-2\right)=0\)
\(\left(x-3\right)\left(x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-1\end{cases}}\)
\(\Rightarrow\text{ }x\in\left\{3\text{ ; }-1\right\}\)
\(\left(x-3\right).2-\left(x-3\right)\left(x+3\right)=0\Leftrightarrow\left(x-3\right)\left[2-\left(x+3\right)\right]=0\)
\(\Leftrightarrow\left(x-3\right)\left(2-x-3\right)=0\Leftrightarrow\left(x-3\right)\left[\left(-1\right)-x\right]\). Xét 2 trường hợp
Xét 2 trường hợp. \(TH1:x-3=0\Leftrightarrow x=0+3=3\)
\(TH2:\left(-1\right)-x=0\Leftrightarrow x=\left(-1\right)-0=-1\). Vậy \(x\in\left\{-1;3\right\}\)
a. x(x-2)+x-2=0
=> (x-2).(x+1)=0
=> x-2=0 hoặc x+1=0
=> x=2 hoặc x=-1
b. 5x(x-3)-x+3=0
=> 5x(x-3)-(x-3)=0
=> (x-3).(5x-1)=0
=> x-3=0 hoặc 5x-1=0
=> x=3 hoặc x=1/5
b) \(x^2-2x-3=0\)
\(D=b^2-4ac\)
\(\left(-2\right)^2-\left(4\left(1.3\right)\right)=16\)
\(x_{1,2}=\frac{-b-\sqrt{D}}{2a}=\frac{2-\sqrt{16}}{2}\)
\(x=1;-3\)
a) \(x\left(x-2\right)+x-2=0\)
<=> \(\left(x-2\right)\left(x+1\right)=0\)
<=> \(\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy...
b) \(5x\left(x-3\right)-x+3=0\)
<=> \(\left(x-3\right)\left(5x-1\right)=0\)
<=> \(\orbr{\begin{cases}x-3=0\\5x-1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=3\\x=\frac{1}{5}\end{cases}}\)
Vậy...
\(x\left(x-3\right)^3+3-x=0\)
\(\Leftrightarrow x\left(x-3\right)^2-\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left[x\left(x-3\right)-1\ne0\right]=0\)
\(\Leftrightarrow x=3\)
ta có
\(\left(x-3\right)^3-\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left[\left(x-3\right)^2-1\right]=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-3=0\\\left(x-3\right)^2-1=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=3\\\left(x-2\right)\left(x-4\right)=0\end{cases}}\)pt dưới \(\Leftrightarrow\orbr{\begin{cases}x=2\\x=4\end{cases}}\)
vậy x=2 hoặc x=3 hoặc x=4